Effect of daily noise exposure monitoring on annual rates of hearing loss in industrial workers. Issue 6 (30th December 2010) - Rabinowitz, Peter M; Galusha, Deron; Kirsche, Sharon R; Cullen, Mark R; Slade, Martin D; Dixon-Ernst, Christine
Abstract : Objectives: Occupational noise-induced hearing loss (NIHL) is prevalent, yet evidence on the effectiveness of preventive interventions is lacking. The effectiveness of a new technology allowing workers to monitor daily at-ear noise exposure was analysed. Methods: Workers in the hearing conservation program of an aluminium smelter were recruited because of accelerated rates of hearing loss. The intervention consisted of daily monitoring of at-ear noise exposure and regular feedback on exposures from supervisors. The annual rate of change in high frequency hearing average at 2, 3 and 4 KHz before intervention (2000–2004) and 4 years after intervention (2006–2009) was determined. Annual rates of loss were compared between 78 intervention subjects and 234 controls in other company smelters matched for age, gender and high frequency hearing threshold level in 2005. Results: Individuals monitoring daily noise exposure experienced on average no further worsening of high frequency hearing (average rate of hearing change at 2, 3 and 4 KHz=–0.5 dB/year). Matched controls also showed decelerating hearing loss, the difference in rates between the two groups being significant (p<0.0001). Analysis of a subset of intervention subjects matched to controls for initial rate of hearing loss showed a similar trend but the difference was not statistically significant (p=0.06). Conclusion: Monitoring daily occupational noise exposure inside hearing protection with ongoing administrative feedback apparently reduces the risk of occupational NIHL in industrial workers. Longer follow-up of these workers will help determine the significance of the intervention effect. Intervention studies for the prevention of NIHL need to include appropriate control groups.